2005
DOI: 10.1161/01.res.0000178787.59594.a0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in Favor of a Calcium-Sensing Receptor in Arterial Endothelial Cells

Abstract: Abstract-Small increases in extracellular Ca2ϩ dilate isolated blood vessels. In the present study, the possibility that a vascular, extracellular Ca 2ϩ -sensing receptor (CaSR) could mediate these vasodilator actions was investigated. Novel ligands that interact with the CaSR were used in microelectrode recordings from rat isolated mesenteric and porcine coronary arteries. The major findings were that (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
145
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(162 citation statements)
references
References 40 publications
14
145
2
1
Order By: Relevance
“…On the contrary, the hyperpolarization and relaxation in response to 1-EBIO, which activates IK Ca in rat mesenteric arteries, 29,30 did not differ between the 2 strains ( Figure 5C; n=5-6; Figure 5D; Table S1). …”
Section: Hyperpolarization and Relaxation To Sk Ca /Ik Ca Activatorsmentioning
confidence: 89%
“…On the contrary, the hyperpolarization and relaxation in response to 1-EBIO, which activates IK Ca in rat mesenteric arteries, 29,30 did not differ between the 2 strains ( Figure 5C; n=5-6; Figure 5D; Table S1). …”
Section: Hyperpolarization and Relaxation To Sk Ca /Ik Ca Activatorsmentioning
confidence: 89%
“…5 Lately, evidence of a functional CaR in medial and endothelial layers of the blood vessels has been provided. The CaR was detected in whole homogenates from rat subcutaneous small arteries 53 and in endothelial cells from rat mesenteric arteries, porcine coronary arteries, 6 and aorta from rat and sheep. 47,54 Recently, the CaR was shown in immortalized endothelial cells from human aorta, and stimulation of the receptor induced production of NO, the most potent vasodilator.…”
Section: Expression Of the Car In The Cardiovascular Tissuesmentioning
confidence: 99%
“…5 Recently, the CaR has also been detected in endothelial cells and vascular smooth muscle cells (VSMCs) and shown to induce hyperpolarization of the smooth muscle cells. 6,7 Furthermore, several novel studies reported the CaR as a possible regulator of blood pressure. 8 -10 In this review, we summarize the status of research concerning possible roles of the CaR in blood pressure regulation and discuss possible mechanisms for its actions.…”
mentioning
confidence: 99%
“…48 The CaSR and KCa3.1-channel are colocalized in caveolin-poor regions of the EC membrane in those arteries. 45 KCa2.3-channels localize within the caveolae so abundant in ECs and, inter alia, act as signaling platforms. Knockout of the key structural protein caveolin-1 appears to ablate EDHF-mediated relaxation by disrupting Ca 2+ -signaling involving TRPV4 and thus reducing connexin expression, 49 whereas TRPV4-deficient mice also lose EDHF relaxation, have reduced NO-relaxation and decreased blood pressure reduction to systemic ACh.…”
Section: Endothelium-dependent Hyperpolarizationmentioning
confidence: 99%